Weak Solutions in Elasticity of Dipolar Porous Materials - Marin Marin (Mathematical Problems in Engineering, 2008)
The main aim of our study is to use some general results from the general theory of elliptic equations in order to obtain some qualitative results in a concrete and very applicative situation. In fact, we will prove the existence and uniqueness of the generalized solutions for the boundary value problems in elasticity of initially stressed bodies with voids (porous materials).